Perilaku Sosial Pecandu Game Online Di Kalangan Remaja Desa Blang Baru Kecamatan Labuhan Haji Barat Kabupaten Aceh Selatan - Saputra, Ismail (JAROW: Journal of Ar-Raniry on Social Work, 2024)
In this thesis, research will focus on the social behavior of online game addicts among teenagers in Blang Baru Village, West Labuhanhaji District, South Aceh Regency. The aim of this research is to reveal the social behavior of online game addicts, the impact of addicts' social behavior and the efforts made to recover from online game addiction. The method used in the research was descriptive, the number of informants in this study was 14 people. The results of this research show that the behavior of teenagers who become addicted to online games tends to be negative, because they consider playing online games to be a satisfaction that cannot be replaced by other activities. In this way, they ignore the people closest to them such as their parents and the surrounding community. Interacting with people around them becomes ineffective because they rarely communicate, this is because they prioritize their desire to play online games compared to other activities so they ignore things that are not related to online games. The impact of online games on social behavior can be divided into two, namely positive impacts and negative impacts, namely: Positive impacts include: can increase relationships or make friends, as refreshing to relieve stress, train discipline, communication and cooperation, can improve English language skills. Negative impacts include : can increase laziness, waste time so much that it is unproductive, neglect of tasks due to online games, cause addiction/addiction effects, can speak harshly and ignore friends, parents and even society. Forms of social behavior include: instrumental rationality, oriented rationality, traditional actions, and affective actions. Meanwhile, efforts made to recover from online game addiction among teenagers are: limiting playing games, looking for new hobbies, implementing restrictions, reducing teenagers' need to access online games such as reducing internet package quotas.